Earthquake input mechanism for time-domain analysis of tunnels in layered ground subjected to obliquely incident P- and SV-waves. (15th February 2019) - Zhao, Wusheng; Chen, Weizhong; Yang, Diansen; Tan, Xianjun; Gao, Hou; Li, Can
Highlights: The interaction between the input motion and the base condition was investigated. The rigid base is only appropriate for special cases. An earthquake-input method for obliquely incident P- and SV-waves was developed. The closed-form solutions of the applied loads at the boundaries were presented. A new equivalent linear approach to consider soil nonlinearities was proposed. Abstract: Time-domain analyses have been widely used to investigate the seismic responses of tunnels. However, the earthquake-input mechanism which significantly influences the results, is not clearly understood, and most extant studies focused on vertically propagating waves. In this study, a series of numerical calculations were conducted to evaluate the performance of several earthquake-input methods for three typical models. The results demonstrate that the combinations of the model base and the input motion should correctly consider the interaction between the two sides of the boundary. Generally, the incident motion at the inner side of the boundary should be used with an elastic base, whereas the within motion at the boundary can be used with a rigid base. However, the rigid base is appropriate only for cases with a large impedance contrast between the two sides of the boundary and cases without outgoing waves at the boundary. Then, an earthquake-input method for the time-domain analysis of tunnels in layered ground subjected to obliquely incident P- and SV-waves was proposed. In this method, the pure incident motion at the model base is applied with an elastic base, whereas the within motions at the left boundary are applied with a rigid base. In addition, the right boundary is characterized by absorbing-elements. The closed-form solutions of the applied motions at the boundaries were presented. The proposed earthquake-input method was verified by comparing with closed-form solutions for two specific problems.